Evaluasi Kinerja Saham Syariah menggunakan Indeks Sharpe, Treynor dan Jensen Periode 2021-2022 - Yunita, Irni Yunita (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to analyze the performance of shares of Islamic companies on the Jakarta Islamic Index (JII) for the period July - November 2022 using stock transaction data on the IDX for 1 year starting December 2 2021 - November 30 2022. This type of research is descriptive research. The sampling method used is purposive sampling. There are 30 stocks that were sampled in this study. The results showed that Islamic stocks included in the top 5 highest performing of the three Sharpe, Treynor and Jensen indices included: ADRO, ITMG, TPIA, INCO. These three stocks can then be taken into consideration in determining the investment portfolio in Islamic stocks. Keywords : Stock Portfolio Performance, Sharpe Index, Treynor Index, Jensen Index